CCoAOMT positively regulates the biosynthesis of secondary metabolites in Zanthoxylum armatum - Xu, Xiu; Hu, Yingxia; Lai, Yingming; Zhu, Tianhui; Li, Shujiang; Liu, Yinggao; Li, Shuying; Yang, Chunlin; Han, Shan (Frontiers in Agronomy, 2025)
IntroductionThe rust disease caused by the fungus Coleosporium zanthoxyli in Zanthoxylum armatum leads to significant leaf damage. However, the genetic regulatory mechanisms underlying disease resistance in this plant remain unclear.MethodsThrough transcriptome analysis and bioinformatics screening, the candidate gene CCoAOMT was identified as potentially involved in rust resistance. Genetic engineering techniques were employed to construct recombinant plasmids for both overexpression and RNAi mediated of CCoAOMT. Transient transformation and stable transformation methods successfully generated CCoAOMT-RNAi and CCoAOMT-overexpression transgenic plants and calli, respectively.ResultsqRT-PCR analysis revealed that the expression levels of CCoAOMT and six related genes were downregulated in RNAi-silenced plants but upregulated in overexpression lines. Following inoculation with fungal spore suspensions, CCoAOMT-RNAi plants exhibited significantly higher disease incidence and severity indices compared to wild-type controls, whereas overexpression plants showed the opposite trend with reduced susceptibility. Furthermore, total lignin and flavonoid contents were markedly decreased in RNAi lines and increased in overexpression lines relative to wild-type plants. Subcellular localization assays using GFP fusion constructs confirmed dual localization of CCoAOMT protein in both the cytoplasm and nucleus.ConclusionThese findings collectively demonstrate that CCoAOMT enhances rust resistance in Z. armatum by regulating lignin and flavonoid biosynthesis pathways.